Cloud Computing with Python Video Course - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2020)
Get started with Cloud Computing in Python. Topics include: Multi-Cloud, Cloud Computing Service Models, Distributed Computing in the Cloud, Cloud Computing ETL Pipelines, Serverless Soutions with the Cloud, Containers in the Cloud, and Continuous Delivery for ML Engineers.